Weight stigma experiences and self-exclusion from sport and exercise settings among people with obesity - Hendrik K. Thedinga; Roman Zehl; Ansgar Thiel (BMC, 2021)
Abstract Background A central strategy to tackle the health risks of obesity is regular physical activity (PA), exercising and participating in sports. However, people with obesity regularly experience weight-related stigma and discrimination in sport and exercise settings. Research has indicated that they often cope with such experiences by simply excluding themselves from sport and exercise. Meanwhile, self-exclusion as a coping strategy has not been fully understood and it remains unclear to what extent self-exclusion from PA settings is accompanied by general inactivity among people with obesity. The goal of this interview study was to determine to what extent physical inactivity among adults with obesity is the result of weight stigma-induced self-exclusion in and from sport and PA settings. Methods We conducted semi-structured interviews with thirty adult men and women with obesity (average BMI: 40.64) and asked them about experiences with their body, weight stigma and coping behaviours in sport and exercise settings across their lifespans. Employing constant comparative analysis and a thematic network approach, we analysed the interview data to identify the most common reasons for and different strategies of self-exclusion. Results Participants reported that they excluded themselves from sport and exercise settings due to traumatic weight stigma experiences, self-discrimination and fear of stigma, using a variety of strategies. Exposure to discrimination was prevented by selectively avoiding certain settings or strategically frequenting them at certain times only, but also by exercising in 'safe' spaces, e.g. at home. Furthermore, people with obesity reported strategically managing their social relations in order to avoid stigmatising reactions by others in exercise settings, for example by exercising individually and avoiding social PA. Most notably, our results strongly indicate that not all self-excluding coping strategies result in less exercising. Conclusions In order to successfully promote physical activity among people with obesity, the various forms of self-exclusion should be taken into account as pathways of stigma regarding physical activity. People with obesity may exclude themselves from certain PA settings, yet could still be exercising on their own or in other ways. One focus of public health strategies should thus be directed at the potentially socially isolating effects.